Effect Of Risk Based Capital, Claims Ratio, Premium Growth Ratio And Investment Ratio On Premium Income In PT Prudential Life Assurance - Melviana Melviana; Thomas Sumarsan Goh; Elidawati Elidawati; Edison Sagala (Economics and Digital Business Review, 2023)
The company seeks to increase the RBC ratio in order to meet regulatory requirements. The uncontrolled claims ratio shows the company's failure to manage the risks it receives so that it will have an impact on increasing premium income. The company is able to generate commensurate premium growth and increase its premium income. The analytical technique used in this research is a comparative descriptive analysis technique. Primary data were collected and obtained through interviews and observations while secondary data were obtained from literature related to the research topic. Risk Based Capital, Claims Ratio, Premium Growth Ratio, Investment Ratio, and Premium Income are used as research objects.The results show that the claims ratio, premium growth and investment ratio have no effect on premium income at PT Prudential Life Assurance. Risk Base Capital has an effect on premium income at PT Prudential Life Assurance. Risk Base Capital, claims ratio, premium growth and investment ratio have no effect on premium income at PT Prudential Life Assurance.